The effect of thermal annealing on Fe/TiO2 coatings deposited with the help of RF PECVD method. Part I. Chemical and phase composition. Issue 5 (1st April 2017) - Sobczyk-Guzenda, Anna; Owczarek, Sławomir; Batory, Damian; Balcerzak, Jacek; Gazicki-Lipman, Maciej; Szymanowski, Hieronim
Abstract: Results of the studies on chemical structure and phase composition of both non-annealed and thermally annealed iron doped TiO2 coatings are presented. The coatings were synthesized with the help of radio frequency plasma enhanced chemical vapor deposition (RF PECVD) and characterized by iron content in the range of 0–4.76 at%. In these studies, an analysis of both elemental composition and chemical bonding was performed with the help of X-ray photoelectron spectroscopy (XPS). X-ray diffraction (XRD) was applied to determine phase composition and Fourier transform infrared spectroscopy (FTIR) was used as a supplementary source of information. The obtained elemental composition data show that, apart from titanium, oxygen and iron, traces of chlorine as well as substantial amounts of carbon are present in the coatings. While chlorine has originated from plasma decomposition of TiCl4, used as a source of titanium, a presence of carbon is associated with a surface contamination resulting from photocatalytic reactions of TiO2 with the adsorbed carbon dioxide. The results of XPS and FTIR indicate that thermal annealing not only modifies phase composition of these materials, but also affects chemical bonding. Finally, XRD analysis shows that iron content has an effect on the size of coherent diffraction domains present in the films.